Photocrosslinkable natural polymers in tissue engineering - Moon, Seo Hyung; Hwang, Hye Jin; Jeon, Hye Ryeong; Park, Sol Ji; Bae, In Sun; Yang, Yun Jung (Frontiers in Bioengineering and Biotechnology, 2023)
Natural polymers have been widely used in scaffolds for tissue engineering due to their superior biocompatibility, biodegradability, and low cytotoxicity compared to synthetic polymers. Despite these advantages, there remain drawbacks such as unsatisfying mechanical properties or low processability, which hinder natural tissue substitution. Several non-covalent or covalent crosslinking methods induced by chemicals, temperatures, pH, or light sources have been suggested to overcome these limitations. Among them, light-assisted crosslinking has been considered a promising strategy for fabricating microstructures of scaffolds. This is due to the merits of non-invasiveness, relatively high crosslinking efficiency via light penetration, and easily controllable parameters, including light intensity or exposure time. This review focuses on photo-reactive moieties and their reaction mechanisms, which are widely exploited along with natural polymer and its tissue engineering applications.